Volkswagen and UMP form partnership to strengthen ties between automotive and TVET - UMP, PNC (2019)
Pekan, April 30 April – Universiti Malaysia Pahang (UMP) and Volkswagen Group Malaysia (VGM) signed a Memorandum of Understanding (MoU), marking a significant milestone in strategic initiatives between the world's biggest automotive brand and one of Malaysia's leading technical universities.